Goddess Durga and Sacred Female Power - Amazzone, Laura (Hamilton Books, 2012)
Goddess Durga and Sacred Female Power is an exploration of the many faces of the Goddess Durga in ancient and contemporary culture. This book takes us on a pilgrimage to goddess temples and natural shrines, to visit shamans and living goddesses in the Kathmandu Valley of Nepal, and to India for the annual ten-day Durga Festival. The mythology, rituals, philosophy, and spiritual practices of this distinctly female-centered and millennia-old tradition of Durga offer an alternative model of female potential and empowerment, focusing on peace, healing, spiritual liberation, and realization of inherent divinity.